Healthy longevity: a systematic review of nutrological and lifestyle aspects - Junqueira, Rodrigo Augusto Carvalho (2023)
Introduction: In the context of healthy longevity, quality of life, genetic, environmental, and lifestyle factors can determine the life expectancy of human beings. Nutrition is a key component affecting our health, and several studies show that nutrition also has the potential to increase lifespan. Objective: It was to carry out a systematic review of the impacts of nutrology and lifestyle on the longevity of human beings, as well as to point out the main dietary and lifestyle care based on the results of clinical studies. Methods: The systematic review rules of the PRISMA Platform were followed. The research was carried out from April to July 2023 in Scopus, PubMed, Science Direct, Scielo, and Google Scholar databases. The quality of the studies was based on the GRADE instrument and the risk of bias was analyzed according to the Cochrane instrument. Results and Conclusion: A total of 311 articles were found, and 147 articles were evaluated and 47 were included in this systematic review. Considering the Cochrane tool for risk of bias, the overall assessment resulted in 29 studies with a high risk of bias and 51 studies that did not meet GRADE. Most studies showed homogeneity in their results, with X2 =87.3%>50%. There is scientific evidence that nutrients and natural substances of human physiology and biochemistry such as melatonin and coenzyme Q10 control the functions of the immune system. Many metabolic or chronic diseases have been implicated with poor diet and lifestyle. Improved diet quality is associated with reduced all-cause mortality, whereas multivitamins and multimineral supplements can improve life expectancy. Overall well-being is improved when sedentary but sufficiently physically active adults reduce sedentary time and increase physical activity levels. The results of the pandemic indicate there have been a variety of lifestyle changes, physical inactivity, and psychological issues. Still, adults over 40 years old, with children, unemployed, and those living in a macroeconomic region were shown to be more exposed to unhealthy behaviors. The maintenance of dietary intervention through telemedicine can reduce the negative impact of eating habits and physical activity patterns.